Proses Berpikir Mahasiswa Pendidikan Matematika IAIN Bukittinggi Dalam Memecahkan Masalah Geometri - Rahmat, Tasnim (Universitas Islam Negeri Imam Bonjol Padang, 2019)
It is common knowledge that education is spearhead of the progress of a nation. A qualified teacher will form an intelligent generation. Faculty of Tarbiyah IAIN Bukitinggi is one of the campuses that prints graduate teachers. Therefore, pre-service teachers, especially mathematics education students (PMTK) need to be prepared the competency to become a professional teacher. One of them is by looking at their thinking process in solving geometry. The way of thinking each person different, included both man and women thinks. This research is qualitative-descriptive. The instruments used are tests and interviews. The subjects is student at grade 3th who had taken courses in mathematics learning strategies. The thinking process of him is as follows: the subject begins to receive and know the information after reading the given problem. In processing information, subject identifies the problem read and uses different ways of solving problems for each question such as guess and check strategies and simple problem-solving strategies. In storing information, subject writes down the information that is known and the way of completion on the answer sheet. The last thought process step is in recalling the information, subject re-examine what information is written simultaneously at the time the sentence is written